Pengembangan Produk Menggunakan Pendekatan New Product Development di PT. LMN Purwakarta - Rizki Nurfadillah; Hendi Iskandar; Afif Fawa Idul Fata (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
In this study, it will focus on product development where the products that are currently produced, one of which is mustard greens, so because this mustard greens product is in the maturity phase or the peak of the increase, which will automatically if this product continues to be produced, it will decrease.research and development is the method used to conduct this research. In the processing of RND data, various processes in the RND method have been calculated according to the data generated from the questionnaire. For the results that have been determined using the RND method, the value generated from the method is that consumers prefer vegetables that are a new variant of PT LMN. After the sampling, market research conditions related to vegetables that are used as the basis for the questionnaire People want vegetables that have affordable prices with the development of vegetables that have a variety at PT LMN. The steps of HOQ to determine new products at PT LMN are to find the values generated from the questionnaire data that has been distributed and processed using the formulas in the HOQ process. After calculating the HOQ, a new product was produced that would be a variation of PT LMN's product, namely kailan vegetables.